Bardoxolone Methyl: A Comprehensive Review of Its Role as a Nrf2 Activator in Anticancer Therapeutic Applications - Valentina Schiavoni; Tiziana Di Crescenzo; Valentina Membrino; Sonila Alia; Sonia Fantone; Eleonora Salvolini; Arianna Vignini (Pharmaceuticals)
Bardoxolone methyl, also known as CDDO-Me or RTA 402, is a synthetic oleanane triterpenoid that has garnered significant attention as a potent pharmacological activator of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. Nrf2 is a master regulator of cellular redox homeostasis, controlling the expression of genes involved in antioxidant defense, detoxification, and mitochondrial function. By inducing Nrf2 and promoting the transcription of downstream antioxidant response element (ARE)-driven genes, bardoxolone methyl enhances cellular resilience to oxidative stress and inflammation. This mechanism is central not only to its cytoprotective effects but also to its emerging role in oncology. A number of studies investigated the effects of bardoxolone methyl in several malignancies including breast cancer, lung cancer, pancreatic ductal adenocarcinoma, prostate cancer, colorectal cancer, oral and esophageal squamous cell carcinoma, ovarian cancer and glioblastoma. Studies in the literature indicate that bardoxolone methyl exhibits anticancer activity through several mechanisms, including the suppression of cell proliferation, induction of cell cycle arrest and apoptosis, inhibition of epithelial–mesenchymal transition (EMT), and impairment of cancer cell stemness. Additionally, bardoxolone methyl modulates mitochondrial function, reduces glycolytic and oxidative phosphorylation capacities, and induces reactive oxygen species (ROS)-mediated stress responses. In this review, we summarize the available literature regarding the studies which investigated the effects of bardoxolone methyl as anticancer agent.